PENERAPAN PENDEKATAN PENEMUAN TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Syahlan Romadon; Ali Mahmudi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
The purpose of this study is to reveal the effectiveness of learning with guided inquiry approach in term of mathematical concepts understanding, and to find out with approach is more effective between learning with guided inquiry approach and ordinary learning in term of mathematical concepts understanding. This research was quasi-experimental research study whose population covered all grade VIII students of SMP Unggulan Aisyiyah Bantul. Class VIII Hafshah and VIII Hawa were established as the sample. Class VIII Hawa as an experimental class was taught with guided inquiry approach. Class VIII Hafshah as a control class was taught with ordinary learning. The results of the study at a significance level of 5%, shows that the learning with guided inquiry approach and ordinary learning was effective in term of mathematical concept understanding. Learning with guided inquiry approach was more effective than ordinary learning in term of mathematical concept understanding.